The Indian Ocean : perspectives on a strategic arena - Booth, Ken (Nova Scotia : Centre for Foreign Policy Studies, 1984)
Proceedings of a conference held in Kalifax, N. S., Oct. 14-16, 1982
Keywords: Indian Ocean Region -- Foreign relations -- Congresses; Indian Ocean Region -- Politics and government -- Congresses; Indian Ocean Region -- Strategic aspects -- Congresses